Analysis of the Effect of Economic Growth, Provincial Minimum Wages and Health Levels on Poverty in West Sumatra for the 2000-2022 Period - Ramadhan, Deary; AMS, Bintang Rizky; Sufiawan, Nur Ari; Weriantoni, Weriantoni (Jurnal Ekonomi Balance, 2023)
Poverty is a complex problem and has a multidimensional nature. As a result, poverty alleviation efforts cover and integrate various aspects of people's lives and must be carried out in an integrated manner. This study aims to determine what factors influence poverty in West Sumatra Province in the 2000-2022 period. The type of data used in this research is secondary time series data of 23 years from the period 2000-2022. Poverty is the dependent variable and Economic Growth, Provincial Minimum Wage, and Health are Independent Variables. The method used in this study is the multiple linear regression analysis model or the ordinary least squares (OLS) method. Data sources were obtained from BPS Indonesia and the World Bank. The results showed that for the variable economic growth has a negative and insignificant effect on poverty in West Sumatra Province, but for the Provincial Minimum Wage variable it has a negative and significant effect on poverty in West Sumatra Province and the life expectancy variable has a positive and insignificant effect on poverty in the Province West Sumatra.